Trombectomia na angioplastia primária em ponte de safena - De Carvalho, Fábio Cardoso [UNESP] (2009)
Thrombectomy in primary angioplasty has demonstrated good early clinical and angiographic outcomes, preventing distal embolization and the no-reflow phenomenon and optimizing myocardial perfusion. This technique is frequently used in native coronary arteries and is rarely reported in coronary grafts. We report the case of a 67-year-old male patient with acute myocardial infarction related to the occlusion of a saphenous vein graft submitted to thrombectomy with good results.